High Prevalence of Unhealthy Alcohol Use Among Persons with HIV, Viral Non-suppression and Any Alcohol Use in Mbarara, Uganda: A Brief Report - Rebecca J. Fisk-Hoffman; Allen Kekibiina; Winnie R. Muyindike; Huimin Cheng; Patrick Agumenaitwe; Ve Truong; Olivia Allison; Natalia Gnatienko; Judith I. Tsui; Judith A. Hahn; Nneka Emenyonu; Leah Forman; et al. (AIDS and Behavior, 2026)
Unhealthy alcohol use is associated with HIV viral non-suppression. It is unclear how common unhealthy alcohol use is among non-suppressed persons with HIV (PWH) who drink alcohol. We conducted chart reviews to recruit PWH in Uganda with recent viral non-suppression for a study on the efficacy of gabapentin for promoting viral suppression among those with unhealthy alcohol use. Of the 288 PWH screened, 87% self-reported unhealthy alcohol use on the Alcohol Use Disorders Identification Test-Consumption and 73% tested positive for urine ethyl glucuronide. These data suggest that alcohol interventions are needed among Ugandan PWH with viral non-suppression and who drink.
Keywords: Sustained virologic response; Alcohol drinking; Uganda